Late infantile form of multiple sulfatase deficiency. (23rd September 2020) - Mohammadian Khonsari, Nami; Hakak-Zargar, Benyamin; Voth, Tessa; Noorian, Shahab
Abstract : Summary: Multiple sulfatase deficiency (MSD) is a lysosomal storage disorder (LSD) that results in the accumulation of sulfate esters which go on to cause neurological deterioration and mental delay, skin changes, and dysmorphism. The disease can be categorized into three subtypes based on the age of onset: neonatal, late infantile, or juvenile. Our patient is a 2.5-year-old girl, the only child of a healthy couple. Prior to the presentation of the disease, she had not been noted to have any previous health complications. The condition began at the age of 6 months with developmental regression and global hypotonia. Following thorough evaluation and testing, the patient was diagnosed with severe late infantile MSD, although some features, such as minimal mental deterioration, minimal dysmorphic facial features, and minimal organ enlargement, did not fully correlate with the diagnosis, since in cases of severe forms of the condition these features are almost always quite marked. The unexpected minimalism of some of the patient's MSD signs in spite of the severity of her MSD condition made her case worth further studying. Learning points: Treating dermatologic signs and symptoms greatly eased our patient's discomfort. We would suggest the use of appropriate supportive treatment for symptom management regardless of the life expectancy of the patient. As regards the diagnosis of MLD, given that in some cases the patient may present with irregular features of the condition, a genetic evaluation may be useful for accurate diagnosis. If motor function impairment is followed by dermatologic involvement, as seen in our patient and in many cases in the literature, MSD must be considered, and additional tests should be done to rule it out.